2021
DOI: 10.1088/1361-6528/ac2d0c
|View full text |Cite
|
Sign up to set email alerts
|

C-amidation of substituted β3 oligoamides yields novel supramolecular assembly motif

Abstract: N-acylated substituted β 3 oligoamides are known to form unique supramolecular nanorods based on a 3-point hydrogen bond self-assembly motif. This motif is an intermolecular extension of the hydrogen bonding network that stabilizes the 14-helix secondary structure unique to β 3 oligoamides. Acetylation of the N-terminus of the molecule provides the necessary third hydrogen bond pair of the motif. Here, the possibility of introducing the third hydrogen bond pair via amidation of the C terminus is investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…18 The mechanisms of head-to-tail self-assembly of helical beta oligoamide units were established previously. [19][20][21][22][23][24] Supramolecular self-assembly of b 3 oligoamides is achieved by modification of either termini to form at least one amide moiety in terminal position. 19,24 The resulting geometrically defined three point hydrogen bonding motif implements supramolecular specificity of the attachment, yielding helical nanorods that can reach millimeter lengths and with only B0.5 nm diameter with high stability 19 and the ability to coassemble.…”
Section: àmentioning
confidence: 99%
See 4 more Smart Citations
“…18 The mechanisms of head-to-tail self-assembly of helical beta oligoamide units were established previously. [19][20][21][22][23][24] Supramolecular self-assembly of b 3 oligoamides is achieved by modification of either termini to form at least one amide moiety in terminal position. 19,24 The resulting geometrically defined three point hydrogen bonding motif implements supramolecular specificity of the attachment, yielding helical nanorods that can reach millimeter lengths and with only B0.5 nm diameter with high stability 19 and the ability to coassemble.…”
Section: àmentioning
confidence: 99%
“…[19][20][21][22][23][24] Supramolecular self-assembly of b 3 oligoamides is achieved by modification of either termini to form at least one amide moiety in terminal position. 19,24 The resulting geometrically defined three point hydrogen bonding motif implements supramolecular specificity of the attachment, yielding helical nanorods that can reach millimeter lengths and with only B0.5 nm diameter with high stability 19 and the ability to coassemble. 23 It was also demonstrated that the terminal loops are sufficient to propagate self-assembly, with the option of including a ''payload'' of other (i.e.…”
Section: àmentioning
confidence: 99%
See 3 more Smart Citations